Short-term manual compression of hemodialysis fistula leads to a rise in cerebral oxygenation - Kovarova, Lucie; Valerianova, Anna; Michna, Martin; Malik, Jan (The journal of vascular access, 2021)
BACKGROUND: Decreased cerebral perfusion and oxygenation are common in hemodialysis patients. Magnitude of the arteriovenous fistula involvement in this phenomenon is not known. The aim of this study was to investigate the effect that a short-term arteriovenous fistula flow interruption has on cerebral oxygenation and to review and suggest possible explanations. METHODS: In 19 patients, basic laboratory and clinical data were obtained and arteriovenous fistula flow volume was measured by ultrasonography. Baseline regional cerebral oxygen saturation (rSO2) was measured by near-infrared spectroscopy. Manual pressure was then applied on the fistula, resulting in total blood flow interruption. After 1 min of manual compression, rSO2 and blood pressure values were noted again. The compression-related change in rSO2 was assessed, as well as its association with arteriovenous fistula flow volume, blood pressure, and other parameters. RESULTS: Mean cerebral rSO2 increased after arteriovenous fistula compression (from 53.6% ± 11.4% to 55.6% ± 10.8%; p = 0.000001; 95% confidence interval = 1.39-2.56). The rSO2 increase was higher in patients with lower rSO2 at baseline (r = -0.46; p = 0.045). CONCLUSION: A significant rise in cerebral oxygenation was observed following the manual compression of arteriovenous fistula. Therefore, the arteriovenous fistula could have a role in impaired cerebral oxygenation in hemodialysis patients.
Keywords: regionální krevní průtok; Male; Oxygen; biologické markery; Cerebrovascular Circulation; blízká infračervená spektroskopie; Biomarkers; mozkový krevní oběh; Regional Blood Flow; dialýza ledvin; Aged; mužské pohlaví; senioři; Arteriovenous Shunt, Surgical; rychlost toku krve; arteriovenózní zkrat; Time Factors; Renal Dialysis; lidé; kyslík; ženské pohlaví; Humans; časové faktory; Pressure; tlak; Female; lidé středního věku; Blood Flow Velocity; Spectroscopy, Near-Infrared; Middle Aged